Enhancing CsSn0.5Ge0.5I3 Perovskite Solar Cell Performance via Cu2O Hole Transport Layer Integration - Rayhan, Abu; Khan, M. A.; Islam, Md. Rabiul (International Journal of Photoenergy, 2024)
Perovskite solar cells (PSCs) have emerged as a promising alternative to traditional silicon solar cells due to their low cost of fabrication and high power conversion efficiency (PCE). The utilization of lead halide perovskites as absorber layers in perovskite solar cells has been impeded by two major issues: lead poisoning and stability concerns. These hindrances have greatly impeded the industrialization of this cutting-edge technology. In light of the harmful effects of lead in perovskite solar cells, researchers have shifted their attention to exploring lead-free metal halide perovskites. However, the present alternatives to lead-based perovskite exhibit poor performance, thus prompting further inquiry into this matter. The primary objective of this research is to investigate the use of Cu2O as a hole transport layer in combination with lead-free metal halide perovskite (CsSn0.5Ge0.5I3) to achieve superior performance. Through meticulous experimentation, the suggested model has achieved outstanding results by optimizing several key variables. These variables include the thickness of the absorber layer (CsSn0.5Ge0.5I3), defect density, and doping densities, as well as the back contact work function and the operating temperature associated with each layer. The proposed FTO/PC60BM/CsSn0.5Ge0.5I3/Cu2O/Au solar cell structure surpassed prior configurations by comprehensively examining key aspects such as absorber layer thickness and defect density, doping densities, and back contact work. The structure has been also compared with multiple electron transport elements and concluded that the proposed model functions superior due to the use of PC60BM as an electron transport layer and it has an improved electron extraction procedure. Finally, the proposed model has achieved the optimized values as Jsc of 31.56 mA/cm-2, Voc of 1.12 V, FF of 81.47%, and PCE of 27.72%. As a consequence of this research, the investigated structure may be an excellent contender for the eventual creation of lead-free solar power cells made from perovskite.